Predictors of late initiation for prenatal care in a metropolitan region in Belgium. A cohort study. Issue 6 (June 2015) - Fobelets, M.; Beeckman, K.; Hoogewys, A.; Embo, M.; Buyl, R.; Putman, K.
Abstract Objectives Timely initiation of prenatal care (PNC) in the first pregnancy trimester allows prevention, identification and treatment of risk factors. However, not all women initiate PNC timely, especially women in a deprived situation. The aim of this study was to measure the prevalence of late initiation, defined as initiation after 14 weeks of gestational age. Secondly the authors wanted to identify predictors for late PNC onset. Study design Observational cohort study. Methods Pregnant women (n = 1750) were recruited in all four hospitals in Ghent (Belgium), a metropolitan region. A socio-economic deprivation ranking was measured by using a General Deprivation Index (GDI), which consists of six criteria to assess a socio-economic situation as deprived. A univariate analysis and a forward conditional multivariate logistic regression model were used analysing the association between deprivation and the likelihood to initiate PNC late. Results 1115 women were included of whom 6.1% (n = 68) initiated PNC late. A foreign maternal country of birth (OR 2.10; 95% CI 1.15–3.83) and a total GDI ≥3 (OR 4.40; 95% CI 2.36–8.21) were good predictors for late initiation. More specifically, the GDI criteria education (OR 4.02; 95% CI 2.00–8.08) and unemployment (OR 2.40; 95% CI 1.17–4.90) were significantly associated with higher likelihood for late initiation. Conclusions A small group of women initiates PNC late. Vulnerable groups, at risk for late initiation can be identified through assessing their deprivation status. Priority for additional support should be given to women with low educational attainment or women in uncertain employment situations.